2021
DOI: 10.3390/vaccines9121476
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Decisions to Vaccinate Children against COVID-19: A Scoping Review

Abstract: Since 2019, the COVID-19 pandemic has resulted in sickness, hospitalizations, and deaths of the old and young and impacted global social and economy activities. Vaccination is one of the most important and efficient ways to protect against the COVID-19 virus. In a review of the literature on parents’ decisions to vaccinate their children, we found that widespread vaccination was hampered by vaccine hesitancy, especially for children who play an important role in the coronavirus transmission in both family and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 77 publications
8
52
3
1
Order By: Relevance
“…This finding is consistent with a previous study which showed that undergraduate parents are more enthusiastic to vaccinate children than parents with higher education [ 12 , 28 , 31 ]. This finding is also congruent with previous studies which concluded that parents’ educational level is one of the determinants of willingness to vaccinate children [ 20 , 32 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with a previous study which showed that undergraduate parents are more enthusiastic to vaccinate children than parents with higher education [ 12 , 28 , 31 ]. This finding is also congruent with previous studies which concluded that parents’ educational level is one of the determinants of willingness to vaccinate children [ 20 , 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…For example, almost half of parents who believe that COVID-19 vaccines are safe on children had vaccinated their children. This result is similar to the rates found in a previous scoping review [ 32 ]. On the other hand, only one-fifth of parents who don’t trust safety of COVID-19 vaccines on children had vaccinated their children.…”
Section: Discussionsupporting
confidence: 91%
“…This contrasts with studies of the general population, where parents were less likely to vaccinate compared to non-parents [126,127]. Among parents, being an HCW is associated with a willingness to vaccinate children [128,129]. This has been observed among the general public and may be related to socioeconomic factors [130].…”
Section: Demographics Of Vaccine Hesitant Hcwsmentioning
confidence: 85%
“…Although the majority of the parents who participated in a Brazilian study were willing to accept COVID-19 immunization for their children, more than half were concerned about serious side effects of COVID-19 vaccines and one third were concerned about their safety [ 8 ]. Furthermore, a literature review found that the main reasons for parents’ hesitancy about vaccinating their children against COVID-19 were fears of side effects and safety concerns [ 48 ]. Moreover, concerns about the safety profile of COVID-19 vaccines has been identified as a factor in vaccination hesitancy among the general population [ 49 ], the elderly [ 50 ], and pharmacy students [ 51 ].…”
Section: Discussionmentioning
confidence: 99%